Kekerabatan Bahasa Kerinci, Melayu Jambi, dan Minangkabau - Monita Sholeha; Hendrokumoro Hendrokumoro (Magister Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2022)
This research investigates the genetic relationship between Kerinci, Jambi Malay, and Minangkabau languages by looking at the proportion of genetic relationship, separation time, and sound changes in those three languages. The theory used in this research is Keraf's (1996) theory and Crowley & Bowern's (2010) theory. Listening and speaking methods with recording and note-taking techniques were used to provide the data. The data were analysed using grouping methods with lexicostatistics and glottochronology techniques. The results of the analysis are presented using formal and informal methods. This study shows that the three languages are related and come from the same protolanguage. Kerinci and Jambi Malay language are related by 85.5%, Kerinci and Minangkabau language are related by 81%, and Jambi Malay and Minangkabau language are related by 77.5%. Kerinci and Jambi Malay were a single language in 1583—1715 AD, Kerinci and Minangkabau were a single language in 1445—1599 AD, and Jambi and Minangkabau Malay were a single language in 1330—1506 AD. Based on qualitative evidence in the form of sound changes, it can be concluded that Kerinci-Jambi Malay and Kerinci-Minangkabau are at the language level, while Jambi-Minangkabau Malay is at the family level.